The arteriovenous access stage (AVAS) classification - Baláž, Peter; Hanko, Jennifer; Magowan, Hannah; Masengu, Agnes; Lawrie, Katarina; O'Neill, Stephen (Clinical kidney journal, 2021)
BACKGROUND: Key anatomical factors mean that individuals needing arteriovenous access are unique and have different possibilities for fistula creation. The aim of this article is to describe a new classification system for all patients needing haemodialysis vascular access in the upper extremity with the purpose to simplify sharing the information about suitability for surgical access creation depending on vascular anatomy. METHODS: According to the patient's vascular anatomy in right and left superior extremities, patients were separated into three arteriovenous access stages (AVAS). The AVAS was validated by three blinded observers using a sample of 70 upper limb arteriovenous maps that were performed using ultrasound on patients referred for vascular access assessment. A sample size calculation was performed and calculated that for three observers, a minimum of 67 maps were required to confirm significant agreement at a Kappa value of 0.9 (95% confidence interval 0.75-0.99). RESULTS: The Kappa value for inter-rater reliability using Fleiss' Kappa coefficient was 0.94 and all patients fitted into the AVAS classification system. CONCLUSION: The AVAS classification system is a simplified way to share information about vascular access options based on a patient's vascular anatomy with high inter-rater reliability.
Keywords: vascular access; classification; arteriovenous fistula; arteriovenous graft; haemodialysis